Enhanced Detection of High Impedance Faults in Smart Distribution Networks Using Differential Energy Indicators - Syarifuddin, Andi; salmiah, salmiah; Masa, M. Anas; Syahrul, Syahrul; Nurul, Nurul; Pakka, Hariani Ma’tang (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
The detection of high impedance faults (HIFs) plays a crucial role in modern active distribution systems to prevent risks like equipment failures, fire incidents, and disruptions in service, while maintaining a stable power supply. HIFs are challenging to detect due to their low-magnitude and fluctuating fault currents, often falling below the detection thresholds of conventional protection mechanisms. These undetected faults can result in significant safety hazards, economic losses, and compromised system reliability. This study presents an enhanced HIF detection method leveraging differential energy indicators derived from positive-sequence current components during fault events. The proposed approach improves fault detection accuracy and discriminates HIFs from nonfault transients, including load switching, capacitor switching, and nonlinear load effects. The method was validated through simulations on adapted IEEE-13 and IEEE-34 bus systems distribution networks with high distributed generation (DG) penetration. Results demonstrated faster response times (